2019
DOI: 10.11005/jbm.2019.26.4.207
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Fracture Liaison Service in Korea: Where Is It Stand and Where Is It Going?

Abstract: The elderly population growth rate is extremely high in Korean society, and life expectancy is close to 85 years old for women and 80 for men as of people born in 2015. The future hip fracture prediction model of Korea shows that the elderly hip fracture rate will increase by 1.4 times by 2025, which will impose a serious socioeconomic burden on Korean society and become a key issue of public health management. The fracture liaison service (FLS) is defined adequate treatment and services for patients over 50 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…[35] KSBMR has developed a coordinator training program, conducted educational symposia, and offered training sessions every year since 2018. [36] 3.3.2. Funding.…”
Section: Organization 331 Models Of Carementioning
confidence: 99%
“…[35] KSBMR has developed a coordinator training program, conducted educational symposia, and offered training sessions every year since 2018. [36] 3.3.2. Funding.…”
Section: Organization 331 Models Of Carementioning
confidence: 99%
“…A multicentre observational trial to investigate the effect of FLS on awareness of osteoporosis and its treatment improvement has been conducted in 11 regional hospitals across the country. Cha et al reported current efforts to establish FLS in Korea and highlighted implementation challenges, such as the lack of awareness regarding the importance of this system and the lack of support by healthcare systems and health policies [ 97 ].…”
Section: Global Regional National and Local Quality Improvement Initi...mentioning
confidence: 99%
“…In South Korea, hip fracture registry programs have been operating since 2014, and FLS since 2016. The emphasis on early detection and treatment of osteoporosis in Korea by the National Health Examination (NHE) has resulted in a doubling of aBMD examinations for women aged 54 years and 65 years old since 2018 [ 71 ].…”
Section: Geographical Variations In Case-finding Strategiesmentioning
confidence: 99%